EDITORIAL-COMPETENCY BASED MEDICAL EDUCATION (CBME) – A CHALLENGE IN INDIA (Indian Journal of Applied-Basic Medical Sciences, 2020)
Competency Based Medical Education (CBME) has been implemented Pan-India from the academic year 2019-20. The goal of the new curriculum is to have a competent ethical Indian Medical graduate who will acknowledge the social obligations for the health rights of all citizens and work efficiently to achieve it. The CBME document has been meticulously made with new additions of Foundation course, AETCOM (Module), Self Directed Learning, Electives, Early Clinical Exposure, Extra Curricular Activities and sports, & Exit examination other than subject wise competencies. Progressive complexity of predetermined core or noncore competencies in different domains along with proficiency table is specified in this document. It has the freedom of formation of curriculum at the institute and assessment at university level. The features of Competency Based Medical Education are that it is outcome based with behavior, skill and knowledge application. CBME has multiple authentic assessment tools. It has shared responsibility between student and teacher with variable time of completion. In India, Medical Council of India has adopted a hybrid approach of Competency Based Medical Education as different phases are time dependent. To achieve a specific competency, specific period has been given and at the end of every phase summative examination is scheduled. There is no freedom for students to finish the phase early or late which is the distinctiveness of CBME. Early clinical exposure, electives was really much needed in curricula and will be of advantage to curriculum.
Keywords: CBME; Pan-India; AETCOM; Self Directed Learning